2019
DOI: 10.1111/phn.12644
|View full text |Cite
|
Sign up to set email alerts
|

Associations among race, residential segregation, community income, and emergency department use by adults with end‐stage renal disease

Abstract: Objective The purpose of this study was to examine independent and interactive effects of race, community income, and racial residential segregation on the likelihood of ED revisits by persons with end‐stage renal disease (ESRD). Design A retrospective analysis of de‐identified data abstracted from Health Care Utilization and Cost Project's (HCUP) 2014 New Jersey State Emergency Department (ED) Database and American Community Survey (ACS) was conducted. Sample The analytic sample was comprised of 2,859 ED enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Bellatorre et al () are among the first to empirically link segregation to allostatic load and Hao et al () extended segregation to cancer survivors' health‐related quality of life, though Massey () already proposed a theoretical connection between segregation and allostatic load. It should be noted that since 2017, several scholars have reported that segregation is related to the availability of health care resources (Caldwell et al, ), health behaviors (Tempalski et al, ; Thomas‐Hawkins et al, ), and neurological disorder (Pennap et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Bellatorre et al () are among the first to empirically link segregation to allostatic load and Hao et al () extended segregation to cancer survivors' health‐related quality of life, though Massey () already proposed a theoretical connection between segregation and allostatic load. It should be noted that since 2017, several scholars have reported that segregation is related to the availability of health care resources (Caldwell et al, ), health behaviors (Tempalski et al, ; Thomas‐Hawkins et al, ), and neurological disorder (Pennap et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…2 Access to care is also modulated by other social determinants of health, such as race and residential segregation. 30,60 HD patients require regularly scheduled dialysis, which is among the greatest burdens of their disease experience. 1,61 Missed dialysis is associated with ED visits, hospitalizations, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,[18][19][20][21][22][23][24][25] Higher ED utilization was also predicted by the following social determinants of health: racial segregation, lower community income, female sex, Black race, reliance on public transport, and lower health literacy. [26][27][28][29][30] The undocumented and social determinants of health concept subgroups were treated separately to reflect the unique barriers to care that undocumented persons face in the United States, such as their ineligibility for Medicare. 54 Several studies demonstrated an association between undocumented status and higher rates of ED visits.…”
Section: Plain-language Summarymentioning
confidence: 99%
“…22 Similarly, the HEART score may have less power to predict 30-day ED returns among our study cohort because many risks could affect patient short-term ED returns such as no insurance coverage, poor education, less income, and homelessness. [23][24][25][26] The present study cohort might have high psychosocial risk, which could potentially prevent accurate prediction of ED returns. Our findings emphasize that the HEART score may be suitable for only certain clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%